Application of a Halo Fixator for the Treatment of Pediatric Spinal Deformity. Issue 1 (January 2021) - Shaw, K. Aaron; Griffith, Matthew; Schmitz, Michael L.; Brahma, Barunashish; Fletcher, Nicholas D.; Murphy, Joshua S.
Abstract : Background: In spine surgery, the halo fixator was initially utilized to stabilize cervical fusions in patients with poliomyelitis. More recently, the indications for halo fixation have evolved to include stabilization and definitive treatment for upper cervical spine injuries (Jefferson fractures, atlanto-occipital dissociations, odontoid fractures, etc.), treatment of atlantoaxial rotatory subluxation, stabilization of long cervical fusions, and preoperative traction. In the realm of pediatric spinal deformity, halo fixation has proved to be a valuable resource for severe or neglected spinal deformities. In this video article, we demonstrate the application of a halo fixator in a pediatric patient with severe scoliosis. Description: The procedure includes appropriate pin placement in the safe zones of the skull performed under either general anesthesia or local anesthesia. Pins are secured to a halo frame that is sized to be 2 cm larger than the circumference of the skull and are tightened according to age-specific torque guidelines. Alternatives: Alternative treatments vary from cervical spine immobilization to definitive surgical treatment in the spine, or even spinal osteotomies, depending on the underlying spinal pathology. Rationale: The halo fixator works by limiting motion of the cervical spine in flexion, extension, and axial rotation. The halo is also able to control and correct translational injuries of the cervical spine. In the setting of spinal deformity, the halo fixator can also be utilized to overcome the effects of gravity and lengthen the spine. Expected Outcomes: For spinal deformities, the halo fixator can be expected to lengthen the spine and increase deformity flexibility prior to definitive surgical treatment in the spine or growth-friendly spinal instrumentation. Important Tips: Correct identification of safe zones for pin placement is vital to correct pin placement. For pediatric patients, it is important to obtain fixation with a minimum of 6 to 8 pins. Pins should be tightened with use of a torque-limiting wrench, up to no more than 1 in/lb (55.9 mm/kg) per year of age, up to a maximum of 8 in/lb (447.9 mm/kg). Applied traction should be a maximum of 50% of the body weight of the patient. Neurovascular examination is vital following application of weight.